2016
DOI: 10.1021/acs.nanolett.6b02875
|View full text |Cite
|
Sign up to set email alerts
|

Facet to Facet Linking of Shape Anisotropic Inorganic Nanocrystals with Site Specific and Stoichiometric Control

Abstract: Nonclassical growth mechanisms such as self-assembly and oriented attachment are effective ways to build complex nanostructures from simpler ones. In the latter case, the nanoparticle components are electronically coupled; however, control over the attachment between nanoparticles is highly challenging and generally requires a delicate balance between dipole-, ligand-, and solvent-based interactions. To this end, we perform incomplete cation exchange with Ag (Cu) on CdSe-seeded CdS nanorods and tetrapods to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
(47 reference statements)
0
16
1
Order By: Relevance
“…The mechanism for linking was previously reported by Sabyasachi et al 5 and will not be described in detail in this work. It is observed that, without the addition of ODPA, no linking takes place as seen in Figure 2(a), in accordance with the view that the addition of ODPA causes the native surface ligands of the Ag 2 S tip to come off.…”
Section: Representative Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The mechanism for linking was previously reported by Sabyasachi et al 5 and will not be described in detail in this work. It is observed that, without the addition of ODPA, no linking takes place as seen in Figure 2(a), in accordance with the view that the addition of ODPA causes the native surface ligands of the Ag 2 S tip to come off.…”
Section: Representative Resultsmentioning
confidence: 78%
“…We have recently developed a wet-chemical method of covalently joining shape-anisotropic cadmium chalcogenide NCs by introducing a reactive inorganic intermediate through a site-selective nucleation process. The particles are subsequently linked by the spontaneous fusion of the reactive inorganic intermediate domains 5 . Although the technique is still based on an oriented attachment mechanism, there is much less need to consider weak interparticle interactions, thus allowing for more flexibility and control.…”
Section: Introductionmentioning
confidence: 99%
“…[53] However, it is interesting that the present MSM type photodetectors based on the Ag 2 HgS 2 SCRs show linear responses, and they perform equivalent and high responsivities compared with most high-level van der Waals heterojunction photodetectors. [62][63][64][65] In fact, it is also worth noting that the Ag 2 HgS 2 SCRs photodetectors perform better than the InGaAs photodetectors (PDA20C2, Thorlabs, effective wavelength range between ≈800 and 1700 nm, Responsivity = 1 A W −1 , NEP = 2.2 × 10 −11 W Hz −1/2 ) and PbSe photodetectors (PDA20H, Thorlabs, NEP = 1.5 × 10 −10 W Hz −1/2 ) that have been commercially used. The investigations illustrate that the as-made Ag 2 HgS 2 -based photodetectors with extraordinary performance are highly potential for practical applications, especially in weak light photodetection including infrared regions in the future since Ag 2 HgS 2 is an alternatively promising and qualified candidate due to its intrinsic property and excellent photodetecting behavior.…”
Section: Resultsmentioning
confidence: 99%
“…24 Lastly, aspect ratio is also a key parameter when considering the selfassembly of these nanorods into mesostructures, affecting their usage in optoelectronic device applications. 25,26 Despite the significant improvement in synthesis and application of CdSe/CdS NRs, one major obstacle hindering its development is the laborious and time consuming experimental trial and error optimizations involved due to the complex behavior in the experimental parameter space. During the rod-like shell growth, the core size/amount, precursors amount, ligand type/ratio can impact the dimension of the rod and, in turn, optical properties of NRs.…”
Section: Introductionmentioning
confidence: 99%